2000
DOI: 10.1103/physrevb.61.r6447
|View full text |Cite
|
Sign up to set email alerts
|

FerroelectricPbTiO3/BaTiO3

Abstract: We have used laser ablation to grow series of PbTiO 3 /BaTiO 3 ͑PTO/BTO͒ multilayers with a modulation wavelength ⌳ that varies between 50 ÅϽ⌳Ͻ360 Å. Modeling the x-ray-diffraction patterns of the multilayers indicates that the PTO layers are a-axis oriented. The Raman measurements reinforce this interpretation. The soft-mode Raman line shifts abruptly in frequency above ⌳ϭ240 Å due to possible strain relaxation of the multilayer, and the ⌳ dependent position of an asymmetric line in the vicinity of 200 cm Ϫ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…3a, we discuss their different signatures by comparing the spectra to data from the literature for the oxides the nanocomposites consist of, the main compounds being eskolaite (Cr 2 O 3 ) and magnetite (Fe 3 O 4 ). 10,[16][17][18][19][20] We also take into account the spectra of the Cr 2 O 3 nanoparticles previously synthesized and later used to include in the nanocomposites and of Fe 3 O 4 nanocomposites (synthesized following the same method as the one herein reported, but in the absence of the chromium oxide nanoparticles) (see Fig. S2 and S3 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…3a, we discuss their different signatures by comparing the spectra to data from the literature for the oxides the nanocomposites consist of, the main compounds being eskolaite (Cr 2 O 3 ) and magnetite (Fe 3 O 4 ). 10,[16][17][18][19][20] We also take into account the spectra of the Cr 2 O 3 nanoparticles previously synthesized and later used to include in the nanocomposites and of Fe 3 O 4 nanocomposites (synthesized following the same method as the one herein reported, but in the absence of the chromium oxide nanoparticles) (see Fig. S2 and S3 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Superlattices, including BaTiO3/SrTiO3 [1], PbTiO3/PbZrO3 [2][3], PbTiO3/BaTiO3 [4][5], PbZrO3/BaZrO3 [6][7],PbTiO3/SrTiO3 [8] and LaAlO3/SrTiO3 [9] have been well researched in previous work. Firstprinciples calculations were extensively used to investigate interesting properties and design new ferroelectric material before experimental work is performed.…”
Section: Introductionmentioning
confidence: 99%
“…In ideal superlattices with perfectly flat, compositionally abrupt interfaces, first-principles calculations and experimental studies have shown how factors such as strain due to lattice mismatches 1,2,3,4,5,6,7,8,9,10,11,12,13,14 , charge compensation 15,16,17,18 and bonding at the interface 19 can be controlled to enhance the ferroelectric properties of the superlattice. Work by Dawber and coworkers show that the behavior of very short period superlattices may deviate from that extrapolated from longer periods 11 .…”
mentioning
confidence: 99%